Express delivery to the suburbs. Transport Infrastructure and European cities. - Ilias-Nikiforos Pasidis; Miquel-Àngel Garcia-López; Elisabet Viladecans-Marsal (European Regional Science Association (ERSA), 2015)
The main goal of this paper is to provide evidence for the causal effect of the highway and railway infrastructure on the suburbanization of population in European cities. This is considered a major issue in Europe, which has never been studied before at this scale. We constructed a unique population and transport infrastructure dataset covering 579 cities from 29 European countries during the period 1961- 2011. We have included different measures of highways and railways on suburbanization and we have estimated their joint effect using a panel IV approach. Our main specification, where we jointly estimate the effect of highways and railways, suggest that an additional high- way ray displaced approximately 6% of the central city population in European cities during the period 1961-2011 on average, whereas the same estimate for radial railways was roughly 2%. We will also employ the heterogeneity of the European regions and cities in order to detect different patterns of the same effect based on regional and city characteristics. The findings of this paper are novel and yield valuable insights for the European transport and regional policies. 2nd choice theme: G_C. Urban sprawl and shrinkage.
Keywords: R4; O4; 330; suburbanization; cities; Europe; highways; railways; transportinfrastructure; history